Dietary exposure of the Belgian population to emulsifiers E481 (sodium stearoyl-2-lactylate) and E482 (calcium stearoyl-2-lactylate). Issue 5 (4th May 2018) - Bel, Sarah; Struyf, Thomas; Fierens, Tine; Jacobs, Griet; Vinkx, Christine; Bellemans, Mia; Voorspoels, Stefan; De Ridder, Karin
ABSTRACT: A dietary exposure assessment of food emulsifiers E481 (sodium stearoyl-2-lactylate) and E482 (calcium stearoyl-2-lactylate) in the Belgian population was performed. Nationally representative food consumption data from the Belgian National Food Consumption Surveys 2004 (BNFCS2004) and 2014 (BNFCS2014) were used for calculations. A conservative approach (combining individual food consumption data with the maximum permitted level (MPL) of foods (tier 2), was compared with more refined estimates (combining individual food consumption data with actual concentrations measured in food products available on the Belgian market (tier 3)). Estimated daily intakes were compared to the acceptable daily intake (ADI) of the stearoyl-2-lactylates. The results of tier 2 demonstrated that 92% of the children (3–9 years), 53% of the adolescents (10–17 years), 15% of the adults (18–64 years) and 26% of the elderly (64–98 years) had a potential intake higher than the ADI. When replacing the MPL with maximum analysed concentration levels in foods, daily intake estimates decreased dramatically. The estimated daily intake of the food emulsifiers was below the ADI for all age groups, except for a small percentage of children (1.9%) for which the intake exceeded the ADI. The main contributors to the exposure of E481 and E482 were bread, rolls and fine bakery wares.